Prediksi Kinerja Steamflood Dengan Metode Myhill-Stegemeier dan Gomaa di Area R Duri Steamflood (DSF) - Rycha Melysa (Journal of Earth Energy Engineering, 2016)
Steamflood constitutes one of method Enhanced Oil Recovery (EOR) by injected steam with quality and particular flow rate kontinyu into reservoir. Its aim is increase oil mobility at reservoir by downs viscosity to produced passes through producer. Before does simulation exhaustively, there is it is better does to predict performance a steamflood's reservoir by analytic simple one. This studies compares two simple methods in prediction steamflood's reservoir performance by use of data historical on area R Duri Steamflood (DSF). Gomaa's method utilizes many graph have already at previous generalizing but just applies on field with given characteristic limitation. Then Myhill Stegemeier modifies equation that made by Mandl and Volek to interpose that displacement form in reservoir is frontal displacement one dimension yawns to oil. Both of that method have excess and its lack each. Compares two simple methods in predicting reservoir performance steamflood using historical data on the area "R" Steamflood Duri. Gomaa method using some charts that have been generalized before but only apply to the courts to limit certain characteristics. Myhill-Stegemeier then modify the equations created by Mandl and Volek to argue that the form of displacement in the reservoir is a one-dimensional frontal displacement steam to oil. Both methods have advantages and disadvantages of each. Both methods produce a number of different oil recovery. The cumulative oil recovery methods amounted to 1378917 Stegemeiers Myhill-STB (76% of OOIP) and Method Gomaa of the STB 999 072 (55% of OOIP). Comparison of steam-oil (FSO) obtained in Method Myhill is a comparison of cumulative, it is evident from the constant value (FSO) obtained from the first year until the 10th year. Gomaa is different from the method they are relatively oil-vapor ratio (FSO) obtained.